HUBUNGAN PENGETAHUAN DAN PERSEPSI PENGGUNAAN ROKOK ELEKTRIK (VAPE) PADA REMAJA WANITA DI KOTA MEDAN - Fakhreni Fakhreni; Putra Apriadi Siregar (Jurnal Kesehatan, 2023)
The problem of smoking among adolescents is a problem that must be addressed immediately, because the consequences caused are very influential on the development of the younger generation. Electronic cigarettes are one of the new types of cigarettes that contain compounds that are carcinogens, compounds that trigger cancer. The phenomenon that exists today, many adolescent women become users of electronic cigarettes and do not know the dangers of electronic cigarettes. The study aims to determine the relationship between knowledge and perception of electronic cigarette (vape) use in adolescent girls in Medan City. This type of research is quantitative research with a descriptive analysis design design with a cross sectional approach.Sampling technique using porpusive sampling approach. Data was collected using questionnaires through google forms. Data analysis using the Spearman statistical test. The results of the statistical test showed p value = 0.163 > α (0.05), there was no relationship between knowledge and perception of e-cigarette use (vape). The good and bad behavior of a person in the field of health depends on the level of knowledge possessed. The lower the knowledge of adolescents about the dangers of electronic cigarettes, the more potential to become permanent smokers of electronic cigarettes. Efforts to reduce the use of e-cigarettes among adolescents can be done by increasing their knowledge about the dangers of e-cigarettes through health promotion, with health counseling by Puskesmas and the Health Office.